Journalists’ Level of Accountability in Tracking Developmental Projects in Edo State - Onovweghware Henry Ovwigho; Daniel Ofomegbe Ekhareafo (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
This research examines the level of accountability among journalists in Edo State, Nigeria, in monitoring developmental projects, emphasizing media's role in fostering transparency, accountability, and public engagement. It investigates the capacity of journalists to uphold these functions despite challenges such as limited access to information, external influences, and pressures from government and political actors. Through a mixed-method approach combining quantitative surveys and qualitative interviews, the research explored the effectiveness of media accountability in promoting societal development and the strategies employed by journalists to engage the public in the developmental process. Findings indicate that media accountability is crucial for project transparency, yet journalists in Edo State often face constraints, including restricted information access and political intimidation. The study emphasizes the need to domesticate the Freedom of Information Act in Edo State to enable journalists to track developmental projects effectively. Recommendations include implementing stronger regulations to protect journalistic integrity and encouraging collaboration among journalists, civil society organizations, and government entities to enhance transparency and accountability.